2016
DOI: 10.1118/1.4959534
|View full text |Cite
|
Sign up to set email alerts
|

Technical Note: Dose effects of 1.5 T transverse magnetic field on tissue interfaces in MRI-guided radiotherapy

Abstract: The doses on tissue interfaces can be significantly changed by the presence of a TMF during MR-guided RT when the magnetic field is not included in plan optimization. These changes can be substantially reduced or even eliminated during VMAT/IMRT optimization that specifically considers the TMF, without deteriorating overall plan quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 16 publications
4
50
0
Order By: Relevance
“…The dosimetric effect of a transverse magnetic field (TMF) in phantom and patients has been studied extensively . Compared to conventional external beam RT without magnetic field, the magnetic field can generally lead to an altered buildup depth, and a larger, slightly shifted (asymmetric) penumbra arising from tilting of the dose kernel .…”
Section: Introductionmentioning
confidence: 99%
“…The dosimetric effect of a transverse magnetic field (TMF) in phantom and patients has been studied extensively . Compared to conventional external beam RT without magnetic field, the magnetic field can generally lead to an altered buildup depth, and a larger, slightly shifted (asymmetric) penumbra arising from tilting of the dose kernel .…”
Section: Introductionmentioning
confidence: 99%
“…The effect of the magnetic field during MRgRT on the dose deposition has been shown to be influenced by the magnetic field strength, the incident beam energy, the beam entrance angle, and the boundary shape . Studies show that clinically acceptable plans can be achieved with multiple beam configurations over the target, and it has even been suggested that dosimetric effects due to the magnetic field could be used to develop partial breast MRgRT treatments …”
Section: Introductionmentioning
confidence: 99%
“…5,6 The effect of the magnetic field during MRgRT on the dose deposition has been shown to be influenced by the magnetic field strength, the incident beam energy, the beam entrance angle, and the boundary shape. [7][8][9][10] Studies show that clinically acceptable plans can be achieved with multiple beam configurations over the target, [10][11][12] and it has even been suggested that dosimetric effects due to the magnetic field could be used to develop partial breast MRgRT treatments. 13 However, as typical MRgRT workflows include daily imaging and a certain degree of adaptation of the original plan, the patient can be lying on the treatment coach for up to 30 min before treatment delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Raaijmakers et al [2] [3] demonstrated the ERE by MC simulation, which was also validated by film measurement in sold water phantoms. Chen et al investigated the dosimetric effect of ERE at air-tissue and lung-tissue interfaces during intensity modulated radiation therapy (IMRT) [5]. Woodings et al conducted a comprehensive dosimetric characterization of the Elekta 1.5T MR-Linac beam for clinical application [6].…”
Section: Introductionmentioning
confidence: 99%